Contemporary Vlach languages - Klimkowski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2021)
The article discusses three issues regarding the present situation of the Vlach languages spoken by Balkan Vlachs. The first one is the linguistic status of Istro-Romanian, Megleno-Romanian and Aromanian (dialect or language) and, respectively, their relation to the Romanian language. On the basis of Kloss’ theory (1967) of Abstand and Ausbau languages, we consider them to be separate Vlach (Balkan Romance) languages. Consequently, the second issue we deal with is the terminology related to these languages and their internal classification. Examining the terms that are currently used, we recommend the forms Vlashki/Zheyanski, (Meglen) Vlach and Armanian (as the native names of the languages) instead of the traditional names Istro-Romanian, Megleno-Romanian and Aromanian, and also a new term Ramanian for a Vlach variety usually considered to be part of Armanian. As for the third issue, i.e. the spelling systems of the contemporary Vlach languages, we present both traditional and more progressive systems, especially with regard to Armanian and Ramanian.